Aedes japonicus japonicus (Diptera: Culicidae) from Germany have vector competence for Japan encephalitis virus but are refractory to infection with West Nile virus - Huber, Katrin; Jansen, Stephanie; Leggewie, Mayke; Badusche, Marlis; Schmidt-Chanasit, Jonas; Becker, Norbert; Tannich, Egbert; Becker, Stefanie C. (Parasitology research, 2014)
The interplay between arthropod-borne (arbo) viruses and their vectors is usually complex and often exert unique relationships. Aedes japonicus japonicus (Hulecoeteomyia japonica or Ochlerotatus japonicus japonicus), an invasive mosquito species with laboratory proven vector competence for a number of emerging viruses has been newly introduced to Germany and is currently expanding its range throughout the country. On the other hand, West Nile virus (WNV), an emerging arbovirus originating from Africa, is already circulating in several European countries and might soon be introduced to Germany. Because newly introduced and rapidly expanding vector species pose a potential risk for public health in Germany, we assessed the vectorial capacity of German Ae. j. japonicus populations for WNV and Japanese encephalitis virus (JEV). The results indicate that German Ae. j. japonicus are susceptible for JEV but are refractory to infection with WNV. Of 67 Ae. j. japonicus females challenged by feeding of WNV-containing blood, none had measurable amounts of WNV-RNA (0 % infection rate) on day 14 post-infection. In contrast, all females challenged with JEV were positive for JEV-RNA (100 % infection rate) on day 14 post-infection. The reason for WNV resistance remains to be determined but is independent from co-infection with other flaviviruses or the presence of endosymbiotic Wolbachia, since we found no evidence for other flavivirus infections within 1,033 tested A. j. japonicus females from the sampling region, nor detectable Wolbachia infection within 30 randomly selected individuals.
Gesehen am 18.09.2020